IPeer2Peer program: a pilot feasibility study in adolescents with chronic pain. Issue 5 (May 2016) - Ahola Kohut, Sara; Stinson, Jennifer N.; Ruskin, Danielle; Forgeron, Paula; Harris, Lauren; van Wyk, Margaret; Luca, Stephanie; Campbell, Fiona
Abstract : Abstract: Adolescents with chronic pain are often socially isolated, having never met others with chronic pain, and often feel misunderstood by healthy peers. Adolescence is a sensitive period for developing one's sense of self and autonomy, which often occurs in the context of peer relationships. This developmental process is disrupted in adolescents when their chronic pain interferes with their social interactions. Peer mentoring is proposed as a developmentally timely intervention. The aim of this study is to develop and test the feasibility, acceptability, and impact of the iPeer2Peer program. The iPeer2Peer program is a tailored peer mentorship program that provides modeling and reinforcement by peers (trained young adults with chronic pain aged 18-25 years who have learned to successfully manage their pain). This program aimed to enhance self-management of chronic pain in adolescents through 10 Skype video calls over the course of 8 weeks. A pilot randomized controlled trial design using waitlist controls was used in an adolescent chronic pain sample. Twenty-eight adolescents aged 14.8 ± 1.6 years (93% female) completed the trial (intervention: n = 12; control n = 16). Three adolescents completed the intervention after completing their participation in the control arm. The iPeer2Peer program was feasible and acceptable, provided the adolescents were given more time to complete all 10 calls. When compared with controls, adolescents who completed the iPeer2Peer program had significant improvement in self-management skills and their coping efforts were more successful. The iPeer2Peer program is a promising peer mentoring intervention that complements standard care for adolescents with chronic pain. Abstract : This pilot study demonstrates that online peer mentoring for adolescents with chronic pain is feasible, acceptable and, when compared to waitlist controls, improves self-management skills.